Kebolehgunaan Tahaluf dalam Akad Mudharabah: Pembinaan Kerangka Awal Konsep Tahaluf Iqtishadi (Journal of Entrepreneurship and Business, 2021)
Tahaluf is usually discussed from the perspective of tahaluf siyasi. Tahaluf siyasi means agreement between several parties to face the same enemy. In this study, researchers want to study beyond the norms of public thought. There is also discussion of tahaluf in politics, but in economics there is no discussion of tahaluf. Therefore, the construction of tahaluf in the economy or can be stated as tahaluf iqtishadi is important to fill in the knowledge gaps in Islamic treaties. To complete this study, this discussion focused on the agreement made in mudharabah contract. There are three focus areas, namely, security, justice and benefit. From this, it can be explained that the purpose of this study is to examine the concept of tahaluf iqtishadi based on mudharabah contract. This study uses a library research to examine the concept of tahaluf siyasi in mudharabah contract. These data were then analyzed using content analysis. As a result, there are two principles, two characteristics and six conditions of implementing tahaluf as the initial framework for the construction of the concept of tahaluf iqtishadi. These two principles are to defend the truth and to defend the covenant. The other two are the terms of the agreement and the contract is void if it is betrayed. The other six are loyalty, sincerity, wise management, stance, fellowship and confidence.
Keywords: Array; Array; Array